Behavioral Enrichment for Mammals - Woltman, Sandy (Wildlife Rehabilitation Bulletin, 2005)
Behavioral or environmental enrichment that serves to increase the psychological well being of an animal has become as important as proper diet and veterinary care for wild animals in captivity. Enrichment provides positive mental stimulation so that these animals do not become bored in the same environment day after day. It helps prevent injuries by providing safe activities as alternatives to escape attempts or destructive behavior, and it decreases the likelihood of other abnormal, stereotypical behaviors. Without proper stimulation, captive animals often dig, pace, become aggressive toward cagemates, and even self–mutilate. Combining plants and animals decreases stress and encourages natural behaviors, including foraging for food. New and innovative ideas in food presentation, toys, cage furniture, and nesting materials are important in enhancing the lives of animals while they are in the care of wildlife rehabilitators.